Two-phase heat transfer - Shah, Mizra Mohammad, 1941- (Wiley-ASME Press series., 2021)
"The two-phase systems covered in this book include boiling, condensation, gas-liquid mixtures, and gas-solid mixtures. While there are many books on these topics, most of them are concerned mainly with theoretical aspects while information of practical use is addressed only briefly. The very few books that were intended to help the practicing engineers are greatly out of date. I therefore felt that that there was a need for an up-to-date book which emphasized the practical aspects while also addressing the theoretical bases. This book is intended to fulfil this need"--